KEPATUHAN POLA DIET DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK - Endang Wahyuni; Ratna Lestari (MEDIA ILMU KESEHATAN, 2013)
Background of Study: End Stage Renal Disease was ranked in the sixth position as the death causal in all hospital in Indonesia, in 2006 with mortality rate 2521 people. The data according to Depkes DIY in 2007 state that there are 87 new cases of End Stage Renal Disease. In the end stage renal disease, proper nutrition and adequate food will give better quality of life. Preliminary study in the Hemodialysis unit RSUD Panembahan Senopati shows that, 20 patients who run hemodialysis therapy with the diagnosis of end stage renal disease, five of them experienced edema, two patients experienced anorexia, with these data the researcher conclude that there are many patients who do notobey with their diet pattern. So it will make their quality life going decrease, it can be proved by weight loss and weight gain in edema patients. Objective: This Study aimed to know a corellation between the pursuance of diet pattern of end stage renaldisease with patient life quality in Hemodialisa Unit of RSUD Panembahan Senopati Bantul . Methods:This study used analysis descriptive with Cross Sectional design approach. The sample was taken with Consecutive Sampling. It means that 104 patients of end stage renal disease who are under going hemodialysis treatment in RSUD Panembahan Senopati Bantul were involved. Result: Most of the patients who are under going hemodialysis therapyobey in implementing the diet program of end stage renal disease. Most of patients who are suffering end stage renal disease in hemodialysis unit of Panembahan Senopati Bantul local general hospital have a good quality of life. The pursuance of diet pattern with the quality of life in the patient of end stage renal disease has a Significatn Corellation. It was shown by the result of Kendal Taup-value 0,000 < 0,05. Conclusion:There is corellation between the pursuance of diet pattern of end stage renal disease with the quality of life of patients in hemodialysis unit of RSUD Panembahan Senopati Bantul Keyword : The pursuance of diet pattern, Quality of life.